(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Science fiction is a unique literary genre that blends imagination with scientific concepts, often introducing new worlds, technologies, and terminologies. Translating such texts presents significant challenges due to the presence of neologisms, complex scientific ideas, and culturally specific elements. This article explores the main translation methods and strategies used in the context of science fiction. It examines how translators maintain accuracy, preserve stylistic features, and ensure readability while dealing with unfamiliar concepts. The study highlights the importance of balancing fidelity to the source text with creativity in the target language. Furthermore, it emphasizes the role of the translator as both a linguistic expert and a cultural mediator.